The Effect of Sharia Principles Application and Service Againts Customer Satisfaction of Sharia Financial Services Cooperative In Central Java - Muhammad Tho'in (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
The purpose of this research is to know the Application effect of sharia principles and service againts customer satisfaction level of murabahah financing product in sharia financial services cooperative in Central Java. The research method is using multiple linear regression test, t test, F test, and R2 test. The results showed that, from the t test results, the service variables proved to be partially significant effect on customer satisfaction with the result of tcount = 5.821> t table = 2.035. While the application of sharia principles variable While the variable application of sharia principles partially has no significant effect on satisfaction with the result tcount= -0.333> t table = -2.035. Then, from the results of the F test of both variables, it simultaneously proved to have a significant effect on satisfaction with the results of Fcount value 30.613 > F table 4.22. From R2 test, it is found that the influence of both variables is 65,7% against customer satisfaction, means independent variable that is application of sharia principles and service influenced simultaneously equal to 65,7% to dependent variable that is customer satisfaction, while the rest 34,3% influenced by other variables outside the two variables used. Keywords: sharia principles, service, customer satisfaction